2021
DOI: 10.1177/19485506211043379
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Well-Being and Prosociality Around the Globe: Happy People Give More of Their Time and Money to Others

Abstract: Subjective well-being (SWB) is positively related to prosocial giving and helping others, but so far, research has not explored the association of individual aspects of well-being with prosocial behavior across the world. We used a representative sample from the Gallup World Poll across 163 countries from 2006 to 2017 to explore the relationship between each aspect of well-being and prosocial behavior ( N = 1,797,630). We found that different aspects of SWB are not equally associated with prosocial behavior: W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 62 publications
4
30
0
1
Order By: Relevance
“…These findings support the opposite conclusion. Yet the findings are very much in line with a long tradition of philosophical theory, 10,11,39 and a growing body of scientific evidence, [16][17][18] each of which suggest that high levels of well-being require self-transcendence. According to this Pro-Environmental Behavior Increases Subjective Well-Being 13 theory, to truly flourish, people must move beyond a narrow focus on themselves, and seek instead to do good in the world.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…These findings support the opposite conclusion. Yet the findings are very much in line with a long tradition of philosophical theory, 10,11,39 and a growing body of scientific evidence, [16][17][18] each of which suggest that high levels of well-being require self-transcendence. According to this Pro-Environmental Behavior Increases Subjective Well-Being 13 theory, to truly flourish, people must move beyond a narrow focus on themselves, and seek instead to do good in the world.…”
Section: Discussionsupporting
confidence: 81%
“…Many studies have found that morality and societal contribution are central to what people consider a happy and meaningful life, [13][14][15] and doing good things for others has been consistently found to increase individuals' experiences of happiness and meaning in life. [16][17][18] Accordingly, just as pro-social behavior generally increases individual well-being, it stands to reason that pro-environmental behavior (PEB) would as well.…”
mentioning
confidence: 99%
“…This includes sharing, helping, comforting, and a range of positive behaviors resulting in benefits for others, and sometimes cost for the self [43]. Research showed that people who engage in prosocial behaviors, such as spending money on others, sharing resources, giving away one's time and skills to help others, are happier and more satisfied in life [44]. With this, people continue to volunteer and help others since these types of behavior increase people's happiness that led the way to higher well-being and life satisfaction [32].…”
Section: Volunteerism and Prosocial Behaviormentioning
confidence: 99%
“…However, it has been argued that these models ignore the potential influence of emotions on behaviors ( Kim et al, 2013 ; Han et al, 2017 ; Tian and Liu, 2022 ). Recently, an emerging school of thought has explored the impact of subjective wellbeing (SWB) on PEBs from a positive psychology perspective ( Sulemana, 2016 ; Wang and Kang, 2019 ; Kushlev et al, 2021 ; Nguyen et al, 2022 ; Ouyang et al, 2022 ). Specifically, there is a significant correlation between people’s SWBs and their PEBs.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, some scholars suggest that people are happier and more willing to support policies that promote environmental sustainability ( Gowdy, 2005 ; Duroy, 2008 ; Kushlev et al, 2021 ). People with a higher SWB are more willing to sacrifice their interests to protect the environment or are more willing to change their lifestyle to reduce environmental damage ( Sulemana, 2016 ; Solano-Pinto et al, 2020 ; Welsch, 2020 ; Kushlev et al, 2021 ). However, other scholars believe that too much SWB may interfere with motivations ( Diener et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%